2014
DOI: 10.4995/ijpme.2014.2078
|View full text |Cite
|
Sign up to set email alerts
|

Cell Formation Heuristic Procedure Considering Production Data

Abstract: Manufacturing cell formation is one of foremost, and critical aspect of any manufacturing cell design problem. A large number of cell formation methods are developed and research in this area is still in progress. In this paper an attempt has been made by authors to develop a simple, easy to understand and implement cell formation heuristic, having the capability to handle production data viz. operation sequence, production volume, and inter-cell movement cost simultaneously. The results obtained from proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Ideally manufacturing cell is to be formed in such a fashion that each manufacturing cell should act as an independent manufacturing unit. The essence of CF approaches is to eliminate/minimize the inter-cellular movement cost of parts (Arkat and Farahani 2012;Kumar and Sharma 2014;Lian et al 2013;Selim et al 1998). It can simply be achieved by duplicating the machines but duplication of machine involves large capital investment which ultimately adds to the product cost.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ideally manufacturing cell is to be formed in such a fashion that each manufacturing cell should act as an independent manufacturing unit. The essence of CF approaches is to eliminate/minimize the inter-cellular movement cost of parts (Arkat and Farahani 2012;Kumar and Sharma 2014;Lian et al 2013;Selim et al 1998). It can simply be achieved by duplicating the machines but duplication of machine involves large capital investment which ultimately adds to the product cost.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of cell CF approaches have been developed so far, majority of them do not consider production-related data (Boutsinas 2013;Won and Lee 2001). Susanto et al (2009) revealed that 80 % of manufacturing CF approaches are focussed on the arrangement of binary part-machine incidence matrix, whereas more realistic and effective approaches could be developed by considering the various manufacturing flexibility and production-related data (Kumar and Sharma 2014). A little work is observed on CF considering any such data in a simple manner and some of them are summarised in Table 1, whilst on the other hand a large number of literature is available on binary matrix-based cell formation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations